The Effect of Dynamic Capability On New Established Company’s Performance: Mediating Role of Entrepreneurial Creativity - Eduard Alfian Syamsya Sijabat; Arik Prasetya (JPAS (Journal of Public Administration Studies), 2023)
A firm performance resulting from dynamic capability empowerment maintains the survival of newly established companies and established companies   amid intense competition and environmental changes. This study aimed to examine the effect of dynamic capability empowerment in newly established companies on a firm performance mediated by entrepreneurial creativity. Online survey data were collected from 143 newly established shipping agency companies in 22 Indonesian provinces as member of Indonesia shipping agency association. The data were analyzed using WarpPLS 7.0, and analysis unit was  organization represented by managing director. The results showed that dynamic capability empowerment in newly established               companies that emphasize learning capability affect a firm performance with a low significance. Furthermore, dynamic capability empowerment inicreases the firm performance when mediated by entrepreneurial creativity. This  results indicate  that               newly established companies will achieve higher performance by empowering their dynamic capabilities that emphasize learning capability  if it is followed an entrepreneurial creativity breakthrough. The increased performance helps the firm respon to tough competition and unpredictable dynamic environmental changes. The theoretical implication of this study is enriched empirical evidence in examining the relationship between dynamic capability and firm performance. The practical implication of this study is that when a newly established company that limited resources and limited access external resources improves its performance by empowering dynamic capability if it is followed an entrepreneurial creativity breakthrough. This study contributed a new empirical finding to the theory of dynamic capability in newly established companies as the previous studies with this focus are hard to find.